β-glucan content in white oat cultivars grown in different environments - Crestani, Maraisa; Carvalho, Fernando Irajá Félix de; Oliveira, Antonio Costa de; Silva, José Antonio Gonzales da; Gutkoski, Luis Carlos; Sartori, João Francisco; Barbieri, Rosa Lía; Baretta, Diego (Pesquisa Agropecuaria Brasileira, 2011)
βIn the 2007 and 2008 seasons, 15 white oat cultivars were grown in Augusto Pestana, Capão do Leão and Passo Fundo municipalities, state of Rio Grande do Sul, Brazil. It was used a randomized complete block design, with four replicates and 3-m2 plots. Genotype performance varied according to the region and year of cultivation in relation to b-glucan content in the grain. The genotypes Barbarasul, Brisasul, UFRGS 19, UPFA 22, URS 20, URS 22 and URS Guapa had an ideal biotype, comprising high mean b-glucan content, wide adaptability and phenotypic stability. Significant correlations are observed between b-glucan content and grain and industrial yield.
Keywords: Avena sativa; adaptability; functional foods; stability; genotype x environment interaction; grain quality